2018
DOI: 10.3847/1538-4357/aac1b8
|View full text |Cite
|
Sign up to set email alerts
|

The Next Generation Fornax Survey (NGFS). IV. Mass and Age Bimodality of Nuclear Clusters in the Fornax Core Region

Abstract: We present the analysis of 61 nucleated dwarf galaxies in the central regions ( R vir /4) of the Fornax galaxy cluster. The galaxies and their nuclei are studied as part of the Next Generation Fornax Survey (NGFS) using optical imaging obtained with the Dark Energy Camera (DECam) mounted at Blanco/CTIO and near-infrared data obtained with VIRCam at VISTA/ESO. We decompose the nucleated dwarfs in nucleus and spheroid, after subtracting the surface brightness profile of the spheroid component and studying the nu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
35
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 115 publications
8
35
0
Order By: Relevance
“…Both in KKs58 and KK197, we found metal-poor NSCs with metallicities comparable to metal-poor GCs. This is in agreement with a study of 61 NSCs of dwarf galaxies in the Fornax galaxy by Ordenes-Briceño et al (2018) that found that most most dwarf nuclei have colours consistent with metal-poor GCs. They also report a bimodal mass distribution of dwarf galaxy NSCs with peaks at log(M * /M ) ≈ 5.4 and 6.3.…”
Section: Comparison To Other Nucleated Galaxiessupporting
confidence: 93%
See 4 more Smart Citations
“…Both in KKs58 and KK197, we found metal-poor NSCs with metallicities comparable to metal-poor GCs. This is in agreement with a study of 61 NSCs of dwarf galaxies in the Fornax galaxy by Ordenes-Briceño et al (2018) that found that most most dwarf nuclei have colours consistent with metal-poor GCs. They also report a bimodal mass distribution of dwarf galaxy NSCs with peaks at log(M * /M ) ≈ 5.4 and 6.3.…”
Section: Comparison To Other Nucleated Galaxiessupporting
confidence: 93%
“…These values use rough estimates of the host stellar mass, based on integrated magnitudes and a fixed mass-to-light ratio. These ratios are within the scatter for galaxies of similar mass (Ordenes-Briceño et al 2018;Sánchez-Janssen et al 2019a). While the NSC-to-host mass relation appears to be independent of environment (Sánchez-Janssen et al 2019a), the mass ratio itself shows a trend with host stellar mass.…”
Section: Comparison To Other Nucleated Galaxiessupporting
confidence: 55%
See 3 more Smart Citations